The synthesis of novel AIE emitters with the triphenylethene-carbazole skeleton and para-/meta-substituted arylboron groups and their application in efficient non-doped OLEDs. Issue 6 (14th January 2016) - Shi, Heping; Xin, Dehua; Gu, Xinggui; Zhang, Pengfei; Peng, Huiren; Chen, Shuming; Lin, Gengwei; Zhao, Zujin; Tang, Ben Zhong
Abstract : Four novel aggregation-induced emission (AIE)-active luminogens ( p -DPDECZ, p -DBPDECZ, m -DPDECZ and m -DBPDECZ) with triphenylethene-carbazole skeleton and para -/ meta -substituted arylboron groups have been synthesized. Abstract : Four novel aggregation-induced emission (AIE)-active luminogens ( p -DPDECZ, p -DBPDECZ, m -DPDECZ and m -DBPDECZ) with triphenylethene-carbazole skeleton and para -/ meta -substituted arylboron groups have been synthesized. Their structures are fully characterized using elemental analysis, mass spectrometry and proton nuclear magnetic resonance spectroscopy. The thermal stabilities, photophysical properties, electronic structures, and electrochemical properties of these molecules are investigated systematically using thermal analysis, UV-vis absorption spectroscopy, fluorescence spectroscopy, theoretical calculation and electrochemical methods. The effects of donor–acceptor interaction and conjugation degree on the photoluminescent and electroluminescent properties of these compounds are investigated. The results show that these donor–AIE–acceptor type compounds exhibit good thermal stability and electrochemical stability as well as AIE properties. Non-doped fluorescent OLEDs fabricated by using para -linked p -DPDECZ as an emitting layer emits a green light with a turn-on voltage of 4.8 V, a maximum brightness of 30 210 cd m −2 and a maximum current efficiency of 9.96 cd A −1 . While the OLED prepared with meta -linked m -DBPDECZ exhibits efficient blue light emission with a maximum current efficiency of 4.49 cd A −1 and a maximum luminance of 16 410 cd m −2 . The electroluminescence properties of these compounds demonstrate their potential application in OLEDs.